DEVICE, KIT AND METHOD FOR COLLECTING ENDOCERVICAL AND VAGINAL SAMPLES (2021)
The present disclosure provides a device for collection of an endocervical or vaginal sample, as well as a method of using the device to collect a sample a subject and perform an assay. The collection device includes a resiliently deformable ring, a flexible membrane coupled to the ring which defines a collection reservoir, and a retrieval element configured for removal of the device.